2020
DOI: 10.3390/en13164093
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Biogas to Renewable Energy by Microwave Reforming

Abstract: Biogas consists of methane and carbon dioxide, the main components, which are major greenhouse gases that affect global warming. As such, in order to convert greenhouse gas into renewable energy, which is a high-quality fuel, the biogas microwave reforming characteristics were studied and the results are as follows: In the main components of biogas, methane and carbon dioxide, the conversion efficiency of both methane and carbon dioxide increased as the amount of CO2 relatively increased. This is because the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Microwave reforming was also tested for biogas, investigating the effect of the presence of nitrogen and oxygen in the reaction mixture, and it was found that their presence may improve methane conversion [233].…”
Section: Electrically Asssited Reformingmentioning
confidence: 99%
“…Microwave reforming was also tested for biogas, investigating the effect of the presence of nitrogen and oxygen in the reaction mixture, and it was found that their presence may improve methane conversion [233].…”
Section: Electrically Asssited Reformingmentioning
confidence: 99%
“…Ni-containing carrier catalysts have been most commonly used. 7 , 11 However, at temperatures below 300 °C, a reaction does not occur. In the temperature range 300–550 °C, the reaction rate of methane and carbon dioxide is very low, even in active Ni-containing catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The second is processing it to increase the concentration of combustible components. Thermal, catalytic, and plasma , methods are used for this purpose. Ni-containing carrier catalysts have been most commonly used. , However, at temperatures below 300 °C, a reaction does not occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a report issued in 2015 by the PBL Netherlands Environmental Assessment Agency, global CO 2 emission from fossil fuel combustion was about 35.7 Gt, which at the time represented a 1.4% annual increase [4]. To replace fossil-based energy resources, various types of renewable energies have been researched for the past few decades [5][6][7]. However, none of these energy sources are economically feasible as compared with low cost fossil fuels, including shale gas [8].…”
Section: Introductionmentioning
confidence: 99%